IMF Staff papers : Volume 2 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1951)
This paper explains contribution of the September 1949 devaluations to the solution of Europe's dollar problem. After the devaluations, the dollar value of exports to the United States from the devaluing countries in Europe recovered from the low levels of the second and third quarters of 1949, but this recovery, which restored exports in the first half of 1950 approximately to the 1948 level should be attributed in large part to the recovery in the US economy rather than to the devaluations. Between the first half of 1949 and the first half of 1950, Europe's dollar imports declined by one-third. Most of this decline occurred, however, between the second and third quarter of 1949, that is, before the devaluations. With imports generally controlled, the effect of the devaluations appeared much more in the reduction of pressure on the control authorities, the substitution of the price mechanism for at least part of the controls as barriers to imports, and the consequent more rational allocation of the relatively scarce dollars among different uses and different users.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet